Increasing the Investment Capacity of the Indonesian Diaspora - Rifki Khoirudin; Suripto; Indanazulfa Qurrota A’yun (PT FORMOSA CENDEKIA GLOBAL, 2022)
This service aims to provide training to Indonesian diapora residing in China. This is so that the Indonesian diaspora can understand the principles of investment and how to invest. This is important because investing is expected to provide an appropriate return and have an impact on the welfare of the Indonesian diapora. The method used in this service is lecture and discussion. The training begins with material presentations, then continues with questions and answers and discussions based on real problems faced by the Indonesian diaspora. What is obtained in this service is understanding the basic concepts of investment. In addition, it is necessary to know how to invest by understanding investment instruments based on the profile of the level of risk and level of profit. There are three stages that need to be done, namely, 1) compiling and planning life goals; 2) determine the amount of investment; and 3) execution. After running, it is necessary to carry out a review and evaluation stage so that it can invest properly and correctly.